2018
DOI: 10.1055/s-0043-122350
|View full text |Cite
|
Sign up to set email alerts
|

Molekulare Mechanismen der kutanen Photokarzinogenese: ein Update

Abstract: ZusammenfassungUV-Strahlung gilt als primäre Ursache der Photokarzinogenese und trägt somit zur Entwicklung von kutanen Hautkrebsentitäten wie Plattenepithelkarzinom, Basalzellkarzinom und Melanom bei. Durch UV-Strahlung entstehen einerseits typische DNA-Photoprodukte und andererseits indirekte DNA-Schäden durch reaktive Sauerstoffspezies. UV-bedingte DNA-Schäden werden durch die Nukleotid-Exzisions-Reparatur behoben, die somit der Bildung von Mutationen und der Hautkrebsentwicklung entgegenwirkt. Durch Mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Deterioration of keratinocytes is responsible for squamous and basal cell carcinomas, which are the most common types of skin cancer. [ 40 ] In this study, we assessed the UV protection of CeO x @HNTs sunscreen by examining the damage to the HaCat keratinocyte cell line ( Figure a). Cytotoxicity assays showed that cells maintained high viability after CeO x @HNTs sunscreen treatment for 48 h, suggesting this formulation is non‐cytotoxic and can be directly applied to keratinocytes (Figure S11, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Deterioration of keratinocytes is responsible for squamous and basal cell carcinomas, which are the most common types of skin cancer. [ 40 ] In this study, we assessed the UV protection of CeO x @HNTs sunscreen by examining the damage to the HaCat keratinocyte cell line ( Figure a). Cytotoxicity assays showed that cells maintained high viability after CeO x @HNTs sunscreen treatment for 48 h, suggesting this formulation is non‐cytotoxic and can be directly applied to keratinocytes (Figure S11, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Photomedicine can be related to the practice of several medical specialties, including dermatology, surgery, interventional radiology, optical diagnostics, cardiology, circadian rhythm sleep disorders, and oncology (Figure 1B). In fact, melanin pigments protect the body from harmful UV radiation (Ohbayashi and Fukuda, 2020), but too much UV radiation is the main cause of photocarcinogenesis, which contributes to skin cancer (Valejo Coelho et al, 2016;Martens et al, 2018) (see Table 1). Light therapy, also known as phototherapy or bright light therapy, is the use of direct sunlight or artificial light of controlled wavelengths to treat a variety of medical conditions, including seasonal affective disorder, circadian rhythm sleep/wake disorders, cancer, and skin wound infections.…”
Section: Photomedicinementioning
confidence: 99%